(untitled) (Sains Humanika, 2021)
This study presents an experimental Single Case-Single Subject ABA design of a 17-year-old female patient suffering from Systemic Lupus Erythematosus (SLE) and Pulmonary Tuberculosis (TB) who experience adjustment disorders. The purpose of this study is to reduce adjustment disorders in the patient with SLE and pulmonary TB by using art therapy. The assessment methods are observation, interviews, and psychological testing tools. Data analysis was carried out using the qualitatively and quantitatively. Quantitative analysis is performed using visual inspection by looking at the comparison of Depression Anxiety Stress Scale (DASS) scores. Initial measurements using DASS showed a level of depression with a score of 26 (severe), anxiety score at 23 (very severe), and stress score at 19 (moderate). Art therapy is given as a therapeutic intervention for the patient. After the therapy was given, there was a decrease in the DASS score with a depression score to 20 (moderate), anxiety score at 19 (severe), and stress score at 17 (mild). The patient also felt moreable to express and control emotions more precisely. These results indicate that art therapy is one of the interventions that can overcome psychological problems in the patient with adjustment disorders.